Complex encounters: nanoparticles in whole blood and their uptake into different types of white blood cells. (May 2013) - Baumann, Daniela; Hofmann, Daniel; Nullmeier, Sven; Panther, Patricia; Dietze, Claudia; Musyanovych, Anna; Ritz, Sandra; Landfester, Katharina; Mailänder, Volker
Aim: A whole blood assay for evaluating the uptake of nanoparticles into white blood cells in order to close the gap between basic studies in cell culture and pharmacokinetic studies in animals was developed.Materials & methods: After drawing peripheral blood into standard blood collection vials with different anticoagulants, amino- and carboxy-functionalized polymeric styrene nanoparticles were added and uptake was evaluated by flow cytometry.Results: By counterstaining surface markers of leukocytes (e.g., monocytes, neutrophil granulocytes, B or T lymphocytes), investigations of different cell types can be conducted in a single run by flow cytometry. The authors demonstrated that anticoagulation should be done with heparin, and not EDTA, in order to prevent hampering of uptake mechanisms.Conclusion: By using heparinized whole blood, the authors demonstrated differences and usefulness of this assay for screening cellular uptake as it should occur in the bloodstream. Nevertheless, animal studies are warranted for final assessment of the nanoparticles. Original submitted 11 November 2011; Revised submitted 1 July 2012; Published online 31 August 2012